Femtosecond laser induced ultrafast interface dynamics between single layer graphene and quartz substrate: A theoretical study - Runping Zhao; Xia Wang; Lei Wang (AIP Advances)
SiO2 is the most widely used dielectric substrate for graphene devices. Theoretically investigating the interaction between graphene and SiO2 is vitally important for understanding graphene properties and improving device performance. In recent years, density functional theory (DFT) has been used to investigate the graphene–SiO2 interaction in ground states. However, the strong interface dynamics for an excited graphene–SiO2 system in ultrafast nonequilibrium processes was rarely researched. In this work, a real-time time-dependent density functional theory (rt-TDDFT) method was adopted to study the femtosecond laser induced ultrafast structure evolution and the underlying dynamics mechanism of the interface between a single layer graphene and a Si-terminated quartz substrate. This work indicates that rt-TDDFT is a promising method to study the strong electron dynamics and the coupled nuclear dynamics for graphene-SiO2 interfaces under ultrafast optical excitation, which benefits graphene device designs and mechanism analysis.